RESPON REGENERASI BEBERAPA GENOTIPE DAN STUDI TRANSFORMASI GENETIK TOMAT (Lycopersicon esculentum Mill.) MELALUI VEKTOR Agrobacterium tumefaciens - Tri Joko Santoso; A Sisharmini; M Herman (Jurnal Agroekoteknologi, 2010)
ABSTRACTThe development of an effective Agrobacterium transformation for tomato depends on several factors including plant genotype, explant vigor, Agrobacterium strain, selection system and culture conditions. It has been reported that tomato genotype contributed to success of transformation and regenerability in tissue culture. The purpose of this experiment was to study of regeneration response of four tomato genotypes and genetic transformation of tomato through Agrobacterium tumefaciens vector. The experiment of tomato genotype regeneration study was conducted at Biotechnology Laboratory, Asian Vegetables Research and Development Center (AVRDC), Taiwan, meanwhile the experiment of tomato genetic transformation study was conducted at Molecular Biology Laboratory, Indonesian Center for Agricultural Biotechnology and Genetic Resources Research and Development (ICABIOGRAD), Bogor. Three of well-adapted genotypes in Indonesia i.e. Intan, Gondol Hijau and CL6046 were used as regeneration response experimental materials. AVRDC’s genotype, CLN1559A, was used as a control genotype in in-vitro culture. The result of experiment showed that there was variation response on the ability of explant to regenerate and form the shoot among the four genotypes. The control genotype, CLN1559, was the most regenerable genotype that indicated by the highest number of regenerated explants and shoots per explants (90,56% and 0,66), followed respectively by Intan (66,22% and 0,37), CLN6046 (45,94% and 0,26) and Gondol Hijau (17,08% and 0,09). Based on the results, among of the well-adapted genotypes in Indonesia, Intan was the most responsive genotype to be regenerated compared with two other genotypes. Considerably, Intan could be used as an explant for study on genetic engineering tomato through A. tumefaciens vector. The results of genetic transformation study have successfully obtained several explants formed the callus dan shoot on medium selection containing 50 mg/l kanamycin. Nevertheless, transformaton efficiency in the experiment still low which of 55,7 explants in average generated 1,7 shoots (about of 3%) that survive on selection medium (50 mg/l kanamycin). Keywords: Lycopersicon esculentum Mill., Regeneration, Genetic Transformation, Agrobacterium tumefaciens